Veneered zirconia inlay-retained fixed dental prostheses: 10-Year results from a prospective clinical study - Rathmann, Friederike; Bömicke, Wolfgang; Rammelsberg, Peter; Ohlmann, Brigitte (Journal of dentistry, 2017)
Objective The purpose of this study was to evaluate the 10-year clinical performance of zirconia-based inlay-retained fixed dental prostheses (IRFDP). Methods For replacement of a molar in 27 patients, 30 IRFDP were luted by use of different cements, Panavia F (Kuraray Europe GmbH) or Multilink Automix (Ivoclar Vivadent GmbH), with use of inlay/inlay, inlay/full-crown, or inlay/partial-crown retainers for anchorage. Frameworks were milled from yttria-stabilized zirconia (IPS e.maxZirCAD; Ivoclar Vivadent GmbH) and fully veneered with pressable ceramic (IPS e.max ZirPress; Ivoclar Vivadent GmbH). Before luting, the IRFDP were silica-coated (Rocatec; 3M Espe) and silanized (Monobond S; Ivoclar Vivadent GmbH). Complications (for example, chipping or delamination of the veneering ceramic, debonding, secondary caries, endodontic treatment, and abutment tooth fracture) and failure were reported, by use of standardized report forms, 2 weeks, 6 months, and 1, 2, and 10 years after cementation. Statistical analysis included Kaplan-Meier survival and success (complication-free survival) and Cox regression analysis (α=0.05 for all). Results During the 10-year observation period, the complications most often observed were chipping of the veneer and debonding. Twenty-five restorations failed and one participant dropped out. Cumulative 10-year survival and success were 12.1% and 0%, respectively. The design of the retainer, use of a dental dam, choice of cement, and location in the dental arch had no statistically significant effect on the occurrence of complications. Conclusions Use of fully veneered zirconia-based IRFDP with this technique cannot be recommended. Clinical significance A large incidence of complications and poor survival were observed for fully veneered zirconia-based IRFDP, revealing an urgent need for further design improvements for this type of restoration. This, again, emphasizes the need for testing of new restoration designs in clinical trials before implementation in general dental practice.